2006
DOI: 10.1097/01.gim.0000204469.30913.67
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein levels in subjects with Prader-Willi syndrome and obesity

Abstract: Purpose: Prader-Willi syndrome is characterized by infantile hypotonia, feeding difficulties, hypogonadism, small hands and feet, mental deficiency, behavioral problems, and hyperphagia leading to obesity in early childhood. To date there have been no studies examining the associated risk of cardiovascular disease related to obesity in Prader-Willi syndrome, nor of circulating biomarkers such as C-reactive protein known to be predictive of cardiovascular disease. Therefore, we have measured the levels of C-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
6
14
1
1
Order By: Relevance
“…Our results demonstrated that CRP levels were significantly higher in PWS obese subjects when compared with non-PWS obese subjects. These results are in agreement with previous studies that demonstrated higher levels of CRP and proinflammatory cytokines, such as IL-18 and IL-6, in obese adults with PWS, in comparison with non-PWS obese subjects (Caixàs et al, 2008; Butler et al, 2006). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results demonstrated that CRP levels were significantly higher in PWS obese subjects when compared with non-PWS obese subjects. These results are in agreement with previous studies that demonstrated higher levels of CRP and proinflammatory cytokines, such as IL-18 and IL-6, in obese adults with PWS, in comparison with non-PWS obese subjects (Caixàs et al, 2008; Butler et al, 2006). …”
Section: Discussionsupporting
confidence: 93%
“…The relationship between CRP levels and BMI in both groups of obese subjects confirms that increased adiposity is associated with a low-grade systemic inflammation in these individuals (Visser et al, 1999; Höybye, 2006; Butler et al, 2006; Caixàs et al, 2008; Viardot et al, 2010). Our results demonstrated that CRP levels were significantly higher in PWS obese subjects when compared with non-PWS obese subjects.…”
Section: Discussionsupporting
confidence: 67%
“…Our study demonstrated the finding of significantly higher levels of hs‐CRP in subjects with PWS when compared with controls, with all nine PWS patients having elevated hs‐CRP > 3 mg/l. This finding is supported by a recent study that found elevated hs‐CRP levels in both PWS subjects and a nonsyndromic obese subject 29 . hs‐CRP has been shown to be significantly elevated in patients dying suddenly with severe coronary artery disease 30 .…”
Section: Discussionsupporting
confidence: 56%
“…This finding is supported by a recent study that found elevated hs-CRP levels in both PWS subjects and a nonsyndromic obese subject. 29 hs-CRP has been shown to be significantly elevated in patients dying suddenly with severe coronary artery disease. 30 The mechanism for elevated hs-CRP in PWS patients is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, published reports on biochemical testing of adults with intellectual or developmental disabilities are few and limited to dehydration and serum concentration of urea and electrolytes (Macdonald et al, 1989); CVD risk factors, such as blood lipids (Bertoli et al, 2006;Braunschweig et al, 2004;Draheim, McCubbin, & Williams, 2002;Draheim et al, 2002a;Rimmer et al, 1994), Creactive protein (Butler, Bittel, Kibiryeva, & Garg, 2006), and blood glucose and insulin (Bertoli et al, 2006;Braunschweig et al, 2004;Draheim, McCubbin, & Williams, 2002;Draheim et al, 2002a); bone health, including vitamin D status and markers of bone remodeling (Center, Beange, & McElduff, 1998;Wong, Lau, Lim, & Fung, 2006;Zubillaga et al, 2006); iron-and copper-related anemias (Molteno et al, 2000;Razagui et al, 1991); vitamins B 12 (Morad, Gringols, Kandel, & Merrick, 2005) and B 6 (Ellman et al, 1986); other nutrient deficiencies (Cole et al, 1985); and appetite and fat-deposition hormones, including leptin (Cento et al, 1999;Hoybye, Barkeling, Espelund, Petersson, & Thoren, 2003;Komori et al, 2004;Proto et al, 2007;Weigle et al, 1997), ghrelin (DelParigi et al, 2002Goldstone et al, 2004Goldstone et al, , 2005, and neuropeptide Y and oxytocin (Hoybye et al, 2003). Table 4 summarizes our review of reports on biochemical assessments of nutritional status and risk in adults with intellectual or developmental disabilities.…”
Section: Biochemical Assessment Of Nutritional Status and Riskmentioning
confidence: 97%